Identifikasi Pemborosan Proses Produksi Sepatu Casual dengan Menggunakan Metode Lean Six Sigma di PT. XYZ - Fanani, Handre Syahrul; Rr. Rochmoeljati, Rr. Rochmoeljati (Universitas Nahdlatul Ulama Blitar, 2025)
PT. XYZ is a manufacturing industry in the field of shoe manufacturing. In the production process, waste is still found that results in defects in shoe products. This can be seen in the shoe production process in 2023 as many as 74200 pairs, there are 1372 pairs of defective shoes. This study aims to determine the waste that occurs in the shoe production process, determine the value of sigma, and minimize defects and waste and reduce activities that do not provide added value. This study used the lean six sigma method. The study began by identifying the waste that occurs in the shoe production process with the most dominant waste, namely defects. The level of sigma capability obtained in the shoe production process at PT. XYZ is 4.10 with a DPMO value of 4646 in the good category for the Indonesian Industry average. Furthermore, analysis was carried out to identify the cause of defects with fishbone diagrams. Proposed improvements using the Failure Mode and Effect Analysis (FMEA) tool. With the design of process activity mapping (PAM) and big picture mapping, lead time can be reduced from 1060.43 minutes to 1000.30 minutes.